PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA DENGAN PENDEKATAN INKUIRI DI SEKOLAH DASAR - Nelsa, Widia Marta (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research was motivated by science learning that is still center on teacher, the learning process has not used teaching approaches that develop thinking skills and scientific attitudes. This research was a class action that aims to describe the planning, implementation and learning outcomes of student in  learning science by the approach of inqury in class IV SDN 02 Indarung. Research includes planning, implementation, observation and reflection. Subject were reseacher (practitioners) and students class IV of SDN 02 Indarung as many as 41 people. The result showed improvement of student learning  outcomes from average 71,43 with a good criterion in the first cycle and increase in the second cycle of 84,73 with the criteria very well. So, the inquiry approach can improve students learning outcomes in science learning in class IV SDN 02 Indarung.   Kata Kunci : hasil belajar siswa,  pembelajaran IPA,  pendekatan  inkuiri, sd